Operational Efficiency and Profitability: A Comparative Financial Performance Analysis of Listed Hospital Corporations (MIKA, SILO, HEAL) on the Indonesia Stock Exchange During the JKN Era - Made Dewi Sariyani; Agnes Ratna Saputri (CV. Get Press Indonesia, 2025)
This study analyzes the operational efficiency and profitability of three leading hospital corporations listed on the Indonesia Stock Exchange: PT Mitra Keluarga Karyasehat Tbk (MIKA), PT Siloam International Hospitals Tbk (SILO), and PT Medikaloka Hermina Tbk (HEAL) during the National Health Insurance (JKN) era. The research addresses the empirical gap where, despite a 20-30% surge in patient volume under JKN, hospitals face a potential 15-20% margin compression due to INA-CBG’s fixed-rate tariffs. The study focuses on the impact of cost structure (Operating Expense Ratio/OER) and capital efficiency (Asset Turnover Ratio/ATR) on profitability. Using a quantitative approach over the 2019–2023 period, the study employs secondary data and applies descriptive and non-parametric statistical analyses (Kruskal-Wallis). Results reveal two distinct strategic models: MIKA’s margin quality strategy, achieving a superior Net Profit Margin (average 18.5%) and the lowest OER (48.34%) through selective non-JKN focus. Conversely, SILO and HEAL adopted a volume-driven strategy, evidenced by higher ATR (0.85x and 0.81x respectively) and BOR (up to 72.1%), but with lower profit margins. Statistical tests confirm significant differences in Return on Assets (p < 0.01) among the three corporations. These findings highlight the critical trade-off between cost control and asset utilization. The study suggests future research focus on granular cost factors and strategic decision-making processes to navigate financial sustainability under universal health coverage systems.